Mempertahankan Pembelajaran Salaf di Pondok Pesantren Salafiyah Parappe Kec. Campalagian Kab. Polewali Mandar - Marfuda Marfuda; Marhani Marhani; Usman Usman; Ahdar Ahdar (Departement of Mathematics Education, 2023)
Since the emergence of modernization or changes in Islamic education in the Muslim world, only a few traditional Islamic educational institutions, such as pesantren (Islamic boarding schools), have managed to survive. Most of them have disappeared or been displaced due to the expansion and transformation of the general education system. Therefore, in such circumstances, it is necessary to reexamine the discussion regarding the efforts of pesantren in preserving their cultural or Salaf learning. This research aimed to: 1) describe the efforts of Salafiyah Parappe Boarding School in sustaining its Salaf learning, and 2) describe the learning strategies employed at Salafiyah Parappe Boarding School, Campalagian Subdistrict, Polewali Mandar Regency. This research adopted a qualitative approach. The object was located at Salafiyah Parappe Boarding School. Data collection was done through interviews, observations, and documentation, which were then analyzed using data reduction, display, verification, and conclusion drawing. The findings of this research indicated that: 1) Salafiyah Parappe Boarding School had successfully made efforts to sustain its learning or Salaf culture by empowering various elements of the pesantren. This had an impact on the existence of the pesantren amidst the development of science and technology. The elements referred to were the boarding house, Kyai (Islamic scholar), Kitab Kuning (classical Islamic texts), mosque, and the students (Santri). 2) The strategies employed by the pesantren to sustain Salaf learning at Salafiyah Parappe Boarding School had two aspects. Firstly, in terms of the learning process, Salafiyah Parappe utilized three methods: bendongan (recitation), sorogan (explanation), and hafalan (memorization). Secondly, in terms of the overall process, the pesantren employed the